Rheological study of natural fiber biocomposites: a review - Durul, Huda; Rezaur, Rahman; Muhammad Khusairy, Bakri; Kuok King, Kuok; Jehan Y., Al-Humaidi; Mohammed Muzibur, Rahman (Springer Nature, 2025)
Rheological properties are pivotal determinants across the materials range, spanning solids, liquids, and gases, elucidating their nuanced deformation responses under applied stresses. This knowledge assumes paramount significance in biocomposite material development, guiding the strategic formulation of these advanced materials. The intricate landscape of rheology unfolds through the exploration of diverse properties, including viscosity, yield stress, and relaxation times, employing multifaceted testing procedures such as dynamic and time–temperature assessments. In biocomposite material research, the seamless integration of matrix and reinforcement materials is a critical focal point. Rheological testing is an indispensable tool, proficiently gauging these distinct materials' complex interactions and binding nature. This paper intricately compiles the literature, explaining diverse testing methodologies and